(untitled) (JED (Jurnal Etika Demokrasi), 2017)
This study aims to improve the learning outcomes of Civics through STAD type cooperative learning model in grade IV students SDN Barrang Caddi Ujung Tanah subdistrict Makassar. This type of research is a Class Action Research consisting of two cycles where each cycle is held four times. The research procedure includes planning, action implementation, observation, and reflection. Subjects in this study were fourth grade students of SDN Barrang Caddi Ujung Tanah Subdistrict of Makassar City as many as 36 students. Data collection techniques used in research are observation and test. The collected data were analyzed with descriptive statistics. The increase of students’ learning outcomes quantitatively can be seen from the average of student learning outcomes in the first cycle is 69.72 with the percentage mastery learning 58.33% is in the low category, increased in cycle II with an average of 81.94 with the percentage of mastery learning reached 88.89% is in the high category. Besides that, there is a change of student activity to the better direction in the learning activity in accordance with the activity monitored through student observation sheet. Based on the results of the above research, it can be concluded that the results of learning Civics fourth grade students SDN Barrang Caddi Ujung Tanah subdistrict Makassar through STAD type cooperative learning model has increased. Keywords: learning outcomes, STAD, students